Bench-scale evaluation of treatment schemes incorporating struvite precipitation for young landfill leachate - Kabdaşli, I.; Safak, A.; Tünay, O. (Elsevier BV, 2008)
In this study, landfill leachate treatment technologies alternative to anaerobic treatment were experimentally investigated. The emphasis was placed upon nitrogen removal through the use of struvite precipitation. Treatment technologies studied included struvite precipitation, low pH (acidic) air stripping, and activated sludge. Dilution of landfill leachate was used as a means to obtain appropriate quality for feeding the activated sludge process in some instances. Five main treatment combinations were applied. The first and second schemes were struvite precipitation followed by activated sludge process which was fed on undiluted and diluted (1:5) effluents. The third scheme was dilution, activated sludge and struvite precipitation. The fourth alternative was acidic air stripping, struvite precipitation and activated sludge process. The fifth scheme was acidic air stripping, activated sludge and struvite precipitation. All treatment schemes provided comparable COD and ammonia removals, all being around 90%. The treatment schemes incorporating the acidic air stripping, however, was found to be the most advantageous in terms of both efficiency and volume and aeration requirements of the activated sludge process since over 80% COD could be removed in the stripping step. Of the fourth and fifth alternative schemes, the fourth was the most efficient, providing 95% removal of both COD and ammonia. Initial dilution of the leachate at a 1:5 ratio was the least effective one, yielding 90% or lower removals for COD and ammonia. The first scheme, namely application of struvite precipitation to raw leachate followed by activated sludge with or without dilution, proved to be a practical system, providing over 85% COD and 99% ammonia removals. High organic loading up to 0.8 g COD/g VSS day was found to be applicable within this scheme.
Keywords: Sewage; Struvite; Magnesium Compounds; Hydrogen-Ion Concentration; Models, Theoretical; Phosphates; Refuse Disposal; Air Pollution; Anaerobiosis; Water Pollutants, Chemical